Advancing the Understanding of Vitamin D Status in Post-Thyroidectomy Hypocalcemia - Gurdeep Singh; Fatima Irshaidat; Christopher Lau; Ariel Pedoeem; Christine Feng; Maria Mohammed Fariduddin; Lei Lei Min; Nidhi Bansal (International Journal of Endocrinology)
Background. Post-thyroidectomy hypocalcemia is the most common complication after total thyroidectomy. Studies to examine the role of low vitamin D in increasing post-thyroidectomy hypocalcemia incidence have produced varying results. This study aimed to assess whether vitamin D deficiency increases the risk of post-thyroidectomy hypocalcemia. Methods. This retrospective study involved 244 patients who underwent total thyroidectomy between 2014 and 2019. Patients were divided into two groups based on pre-operative vitamin D levels. Group A and Group B had pre-operative vitamin D (25-hydroxyvitamin D) levels of ≥20 ng/ml and <20 ng/ml (reference range for vitamin D is 30–100 ng/dl). The effect of vitamin D, gender, body mass index (BMI), and ethnicity on post-operative calcium and PTH levels was analyzed. Results. Post-operative calcium levels for Group A were not statistically different compared to Group B (8.52 ± 0.64 mg/dl vs. 8.45 ± 0.58 mg/dl (mean ± S.D.; p value = 0.352). The average post-operative PTH of the two groups did not differ significantly (Group A: 32.4 ± 27.5 pg/ml; Group B: 34.4 ± 41.7 pg/ml; p value = 0.761). Conclusion. Pre-operative vitamin D levels are not predictive of post-thyroidectomy hypocalcemia.